1986
DOI: 10.1128/mcb.6.10.3523-3530.1986
|View full text |Cite
|
Sign up to set email alerts
|

Site-Specific Mutagenesis of cdc2+, a Cell Cycle Control Gene of the Fission Yeast Schizosaccharomyces pombe

Abstract: The cdc2+ gene of Schizosaccharomyces pombe is homologous to the CDC28 gene of Saccharomyces cerevisiae. Both genes share limited homology with vertebrate protein kinases and have protein kinase activity. cdc2+ has been subjected to mutagenesis in vitro. A null allele of the gene, constructed by insertion of the S. cerevisiae LEU2 gene into a site within the gene, has a phenotype similar to that of many temperature-sensitive alleles of cdc2. Mutations within the predicted ATP-binding site and in a region which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1987
1987
1996
1996

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…For example, Kamps and Sefton found that neither histidine nor arginine could replace this lysine to support the protein kinase activity or transforming potential of Src (Kamps & Sefton, 1986). Comparable mutants of cyclin-dependent kinases, protein kinase C, MAP/ERK kinase, and other protein kinases have also been shown to be nonfunctional in ViVo (Booher & Beach, 1986;Jove et al, 1987;Ohno et al, 1990;Lange-Carter et al, 1993;Mansour et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Kamps and Sefton found that neither histidine nor arginine could replace this lysine to support the protein kinase activity or transforming potential of Src (Kamps & Sefton, 1986). Comparable mutants of cyclin-dependent kinases, protein kinase C, MAP/ERK kinase, and other protein kinases have also been shown to be nonfunctional in ViVo (Booher & Beach, 1986;Jove et al, 1987;Ohno et al, 1990;Lange-Carter et al, 1993;Mansour et al, 1994).…”
Section: Discussionmentioning
confidence: 99%